(untitled) (Open International Journal of Informatics, 2016)
Implementing technology is important to enhance the enterprise information transaction but it is impossible to secure it without organizational and human supports. Information security is about confidentiality, integrity and availability of the data and due to complexity of human resources the users have always exposed the information security to the internal threat. This paper presents a descriptive result regarding the human factors of information security vulnerability in one electrical enterprise in Iran. The result is presented based on the continuation of the previous review work. The descriptive analysis was performed on twenty participants’ response over qualitative investigation. Based on the descriptive scoring result, training, risk communication and emotional control are found to be the most significant factors influencing information security vulnerability. Surprisingly security culture and staff experience were not significantly influential in this study. In regard to future works, an in-depth thematic analysis will be performed in order to have an overall perspective regarding the factors of concern